Entrepreneurship education in Ghana – the case of the KNUST entrepreneurship clinic - Nyadu-Addo, Ralph; Mensah, Mavis Serwah Benneh (Journal of Small Business and Enterprise Development, 2018)
© 2018, Emerald Publishing Limited. Purpose: Entrepreneurship education thrives on the pillars of experiential education. Using the case of the Kwame Nkrumah University of Science and Technology in Ghana, the purpose of this paper is to examine the entrepreneurship clinic (EC) as a viable pedagogy for the promotion of experiential education in entrepreneurship. Design/methodology/approach: The paper relies on insider action research to analyse, within Joplin’s five-step model, the case of the EC at the Kwame Nkrumah University of Science and Technology (KNUST), Ghana. Findings: The analysis showed that the KNUST clinic comprises five main activities including preparation, orientation, selection and matching, coaching and monitoring and evaluation. In relation to Joplin’s five-step model, the first three stages of the clinic provide focus for the clinic while the remaining two stages – coaching and monitoring and evaluation – entail activities that are geared towards action, support, feedback and debrief. Through the clinic, thousands of tertiary students have been trained in entrepreneurship and new venture creation; some selected participants have been coached while others have had the opportunity to qualify for business incubation. Research limitations/implications: Although the paper discusses some achievements of the clinic in relation to enrolment and fundraising, it does not assess the impact of the clinic on the entrepreneurial competencies, intentions and initiatives of participants, hence, these issues are recommended for future research. Practical implications: The paper demonstrates that it is feasible to implement the EC methodology, irrespective of the cost and time implications that are often associated with experiential educational methodologies. However, support from university management, funding raising from internal and external sources and technical support from industry and government agencies are key to the sustainability of clinics. Originality/value: The paper adds novelty to the entrepreneurship education literature by bringing to the fore how a university in an emerging African economy is implementing and managing the EC pedagogy.
KerkoCite.ItemAlsoKnownAs: 10.1108/jsbed-02-2017-0062 10/gf62p2 2129771:8T5MIJXW 2317526:3JJTGLIK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:achievement; F:pedagogy; P:economy; P:measurement; P:technology; R:evaluation; R:impact; T:entrepreneurship education; T:trainee; Z:Clinic; Z:Development; Z:Education; Z:Entrepreneurship; Z:Experiential; _C:Ghana GHA; publicImportV1